The Implementation of Task-Based Language Teaching (TBLT) English Class for Secondary School Students: a Study at Madrasah Aliyah Radhiatul Adawiyah Makassar - Ibnumal Ibnu; Amirullah; Abdul Halim (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This research aimed to explore teahcer’s perception regarding the implementation of cooperative learning in teaching reading to the eleventh-grade students at SMAN 16 Pangkep, a school located on a remote island. The study had four objectives: (1) to investigate the teacher’s perception of cooperative learning in the classroom, (2) to examine how cooperative learning is implemented by the teacher in teaching reading, (3) to identify the benefits and challenges associated with cooperative learning according to the teacher, and (4) to propose solutions to the challenges encountered in its application based on the teacher’s perception. The research was conducted at SMAN 16 Pangkep, focusing on a single subject, the English teacher herself. The instruments included in the research were observations and interviews. The result of the research showed that (1) The English teacher at SMAN 16 Pangkep views cooperative learning as a valuable strategy that fosters collaboration and shared responsibility among students. She actively seeks resources to better implement this method, showing a commitment to effective teaching. (2) In reading classes, cooperating learning involves clear objectives, appropriate texts, and small group activities. (3) Cooperative learning have proven to improve students reading abilities and academic development. However, challenges like managing group dynamics and ensuring equal participation exist. (4) To address these, the teacher uses reflective practices, continually adapting her methods to support all students and promote independent learning and critical thinking.